MICROBES CAUSING SURGICAL SITE INFECTIONS AND THEIR ANTIBIOTIC SENSITIVITY PATTERN IN A TERTIARY CARE HOSPITAL - DR .ANITA SAMRAJ; DR .V.KRISHNAN (International Journal of Pharma and Bio Sciences, 2014)
Surgical site infection continues to be a significant problem due to emergence of resistant microbes for the currently available antibiotics [1][2]. To study the incidence of surgical site infection and antibiotic sensitivity pattern of microbes associated with surgical site infection This retrospective , observational was conducted at saveetha medical college , chennai . Data was obtained from the cases undergone surgery during the year January 2013 to December 2013 and antibiotic sensitivity reports were obtained from the central lab of our hospital and analysed Study shows the incidence of surgical site infection on our hospital is about 14.1% and staphylococcus aureus is the major pathogen associated post operative wound infections . Amikacin showed good sensitivity towards the gram positive and gram negative isolates and Enterococcal spp .showing considerable resistance towards various antibiotics including vancomycin . In this study , overall incidence of wound infection is well within the occurrence mentioned in similar studies , however incidence of dirty , contaminated wounds are more which nessciates revision of antibiotic policy for covering such infected wounds .